Further study of the trace representation of Bent sequences families - KE Pin-hui1; ZHANG Jie2; WEN Qiao-yan2 (Tongxin xuebao)
Linear onto mapping satisfying certain conditions plays an important role in the generation of Bent sequences families.Further discussions were made A well-rounded characterization of these mapping were presented,and known results were showed to be a subcase of our general results.